A comparative study of the cardiopulmonary and sedative effects of a single intramuscular dose of ketamine anesthetic combinations in rabbits. (February 2020) - Cardoso, Clarisse G.; Ayer, Ilan M.; Jorge, Adriana T.; Honsho, Cristiane S.; Mattos-Junior, Ewaldo
Abstract: The aim of this prospective, randomized, blinded crossover study was compare the cardiopulmonary and sedative effects of ketamine in combination with acepromazine, diazepam, dexmedetomidine, midazolam or xylazine, injected intramuscularly in rabbits, using eight one-year-old male New Zealand rabbits (4.1 ± 0.40 kg). All treatments included ketamine (K; 30 mg/kg) in combination with one of the following: acepromazine 0.5 mg/kg (treatment KA); diazepam 1 mg/kg (KD); dexmedetomidine 0.025 mg/kg (KDex); midazolam 1 mg/kg (KM); or xylazine 3 mg/kg (KX) mixed in the same syringe and injected intramuscularly. Cardiopulmonary variables, blood gases and sedative scores were measured before injection (T0 or baseline) and every 10 min thereafter, over a 60-min period. There were reductions in heart rate, compared with the baseline, at all evaluation times in treatment KX. Treatments KDex, KM and KX presented reductions in respiratory rate at all evaluation times, in comparison with the baseline. There were reductions in mean arterial pressure in KA and KX at times T10-T60 and in PaO2 in KDex, KM and KX at T10-T50. The sedation scores were similar in KA, KDex, KM and KX at T10-T20. Ketamine in combination with acepromazine, dexmedetomidine, midazolam or xylazine promoted similar sedative effects for twenty minutes, but the α2-agonists can promote hypoxemia. Highlights: Ketamine in combination with acepromazine, dexmedetomidine, midazolam or xylazine were analyzed after a single IM injection. No sedative differences in rabbits after injection of the KA, KDex, KM and KX; more longer in those treated with KA, KDex or KX. There was significant decrease in oxygenation when dexmedetomidine or xylazine was used.